2016
DOI: 10.1364/ome.6.002487
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature direct growth of graphene patterns on flexible glass substrates catalysed by a sacrificial ultrathin Ni film

Abstract: Direct deposition of graphene on substrates would avoid costly, time consuming and defect inducing transfer techniques. In this paper we used ultrathin films of Ni, with thickness ranging from 5 to 50 nm, as a catalytic surface on glass to seed and promote chemical vapor deposition (CVD) of graphene. Different regimes and dynamics were studied for various parameters including temperature and reaction time. When a critical temperature (700 °C) was reached, Ni films retracted and holes formed that are open to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Since both methods require a transferring process, graphene growth methods that allow for direct formation on silicon substrates have been sought aer and several attempts have been reported. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] In this study, we developed a procedure to grow graphene from a solid-state carbon source directly on silicon substrates. To reduce the complexity of the process, the number of steps, and the cost, we have also developed a direct patterning procedure that allows to produce graphene samples with arbitrary position, size, and shape: notably this procedure does not require any dry etching process.…”
Section: Introductionmentioning
confidence: 99%
“…Since both methods require a transferring process, graphene growth methods that allow for direct formation on silicon substrates have been sought aer and several attempts have been reported. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] In this study, we developed a procedure to grow graphene from a solid-state carbon source directly on silicon substrates. To reduce the complexity of the process, the number of steps, and the cost, we have also developed a direct patterning procedure that allows to produce graphene samples with arbitrary position, size, and shape: notably this procedure does not require any dry etching process.…”
Section: Introductionmentioning
confidence: 99%
“…After drying the structure and storing it overnight in vacuum to remove H2O residues between graphene and the substrate, PMMA is removed by dipping the samples in acetone and isopropyl alcohol (15 min at each solvent). In order to build bilayer graphene structures on top of the BML platform, the PMMA transfer was repeated twice [37]. For graphene growth, we used a Cu foil of 25 µm thickness (Sigma Aldrich, Saint Louis, MO, USA) as a catalytic substrate on which monolayer graphene is deposited by Chemical Vapor Deposition (CVD, Black Magic 4-inch, AIXTRON, Herzogenrath, Germany) under the following conditions: CH 4 :H 2 (1:4), 25 mbar and 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…After drying the structure and storing it overnight in vacuum to remove H 2 O residues between graphene and the substrate, PMMA is removed by dipping the samples in acetone and isopropyl alcohol (15 min at each solvent). In order to build bilayer graphene structures on top of the BML platform, the PMMA transfer was repeated twice [37]. To couple incident light with the surface waves, we use the Kretschmann configuration [38].…”
Section: Methodsmentioning
confidence: 99%
“…For a wider range of practical applications, and also from an energy saving point of view, lower temperature and transfer-free graphene growth are still major challenges in graphene research. For example, Marchena et al have achieved direct graphene growth on exible glass at 700 C. 12 Sulaiman et al and Jang et al demonstrated CVD graphene growth on Cu at 450 and 300 C by using chlorobenzene and benzene, respectively, as a carbon source. 13,14 The ion bombardment of solid surfaces is well-known to entail the formation of nano structures even at room temperature, such as ripples, pyramid, conical protrusions (cones) and whiskers.…”
Section: Introductionmentioning
confidence: 99%